Jaap Bakema and the open society - Boyer, Mary Christine 1939-; Gameren, Dick van 1962-; Hein, Carola 1964-; Sipkes, Jorrit; Reijndorp, Arnold 1948- (Archis Publishers, 2018)
Jaap Bakema and the Open Society' is the first extensive publication on the Dutch architect and the remarkable production of his office Van den Broek and Bakema. His ideas on the open society are extremely relevant to the current debates about how to involve citizens in city building and creating alternative systems to crumbling welfare states. This historical document will highlight both his most relevant and less known work through texts, archival materials and photography. The book contains interviews with his contemporaries such as John Habraken and Herman Hertzberger and essays that each emphasize a different aspect of his work and the context in which it came into being
Keywords: Bakema, Jacob Berend -- 1914-1981; Stadtplanung; Architektur; Offene Gesellschaft; Bakema, Jaap / 1914-1981 / architect; Bakema, Jaap / 1914-1981; Van den Broek en Bakema, Architectenbureau; Architecture / Netherlands / 20th century; City planning / Netherlands / 20th century